DETERMINAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (CSRD) PADA PERUSAHAAN PERTAMBANGAN PERIODE 2014-2018 - Maria Suryaningsih; Mulia Ningsih (JURNAL AKUNTANSI, 2021)
This research has a problem where the company implements corporate social responsibility with the existence of a law, not from awareness. Companies are also not yet aware of the benefits of implementing corporate social responsibility and there are still different previous researchers.This study aims to examine the effect of profitability, leverage, and ownership structure on corporate social responsibility. This study uses data from 15 mining companies listed on the Stock Exchange Index (IDX) during the period 2014 to 2018 using SPSS 24 software. The results showed that profitability had no effect on corporate social responsibility . Leverage has no effect on corporate social responsibility . Ownership Structure has a significant positive effect on corporate social responsibility . That is, high institutional ownership can increase the existence of corporate social responsibility actions and Simultaneously Profitability, Leverage and ownership structures simultaneously have a significant positive effect on corporate social responsibility .